Promoting Resilient and Healthy Cities for Everyone in an Urban Planning Context by Assessing Green Area Accessibility - Rostang, Olivier; Gren, Asa; Feinberg, Adam; Berghauser Pont, Meta (Frontiers in Built Environment, 2021)
Rapid economic development and population growth has led to urban densification and massive land use changes, putting pressure on both ecosystems, and people. In this context, public health issues have become crucial for cities to address to ensure they remain livable and healthy for everyone. Since the health challenges of cities tend to manifest themselves differently among different population groups—e.g., groups of higher socioeconomic status tend to be correlated with better health than groups of low socioeconomic status—closing the health gap has become a priority for creating healthy cities for everyone. More greenness close to where people live and better accessibility to green areas has been shown to be useful for improving human health and for tackling health inequalities. This paper aims at developing a method for supporting urban planners and policymakers on where to geographically prioritize investments in green infrastructure to contribute to closing the health gap and promote community resilience through improving public health. Using the City of Stockholm as a pilot, we apply a GIS analysis to identify vulnerable population groups in relation to geotagged empirical human health- and socio-economic data. By then assessing vulnerable populations in relation to population numbers and accessibility to urban green areas, an Urban Green Opportunity Map (UGOM) was created, identifying focus areas where investment in green infrastructure will contribute most to closing the health gap and building community resilience.